Distributed cognitive maps reflecting real distances between places and views in the human brain - Sulpizio, Valentina; Committeri, Giorgia; Galati, Gaspare (Frontiers in Human Neuroscience, 2014)
Keeping oriented in the environment is a multifaceted ability that requires knowledge of at least three pieces of information: one’s own location (“place”) and orientation (“heading”) within the environment, and which location in the environment one is looking at (“view”). We used functional magnetic resonance imaging (fMRI) in humans to examine the neural signatures of these information. Participants were scanned while viewing snapshots which varied for place, view and heading within a virtual room. We observed adaptation effects, proportional to the physical distances between consecutive places and views, in scene-responsive (retrosplenial complex and parahippocampal gyrus), fronto-parietal and lateral occipital regions. Multivoxel pattern classification of signals in scene-responsive regions and in the hippocampus allowed supra-chance decoding of place, view and heading, and revealed the existence of map-like representations, where places and views closer in physical space entailed activity patterns more similar in neural representational space. The pattern of hippocampal activity reflected both view- and place-based distances, the pattern of parahippocampal activity preferentially discriminated between views, and the pattern of retrosplenial activity combined place and view information, while the fronto-parietal cortex only showed transient effects of changes in place, view, and heading. Our findings provide evidence for the presence of map-like spatial representations which reflect metric distances in terms of both one’s own and landmark locations.